Porušitvena erozija v občini Ajdovščina - možnosti in omejitve uporabe lidarskih podatkov za modeliranje padajočega kamenja - Kobal, Milan (Gozdarski vestnik, 2016)
Rockfall is a consequence rock decay, which is most often shown as rockfall in the nature. Time prediction of rockfalls is practically impossible, but using diverse models we can determine areas of potential rockfall motion and deposition we can assume to be hazard areas. In our research we divided the Ajdovščina Municipality into the area with prevailing calcareous bedrock and the area with flysch occurring as bedrock. Limit values of the slopes, above which the areas were assumed to be potential rockfall sources, come from the literature; for flysch areas 46° and 53° for calcareous bedrock area. The potential rock motion and run-out zones were determined using Conefall model based on the principle of energy line % we applied energy line angle 32° and angle of the cone top % 16°. In modeling we used lidar digital relief model 1 % 1 m. We determined 1524 potential rockfall sources with total area of 102.9 ha. Mean size of the potential rockfall release zone is 260 m2. On the basis of Conefall model results we determined 3379.9 ha of areas where there is probability of rockfall motion or run-out; there are large differences concerning the share of these areas. Lidar data is frequently used in determining potential rockfall sources and has many advantages over other methods, but it also has deficiencies. Some pointless rockfall release areas were determined, while we did not embrace certain potential sources using the tested method. Data processing is, in terms of processing, lavish on a larger area and requires very capable computer software. The best solution for rockfall modeling seems to be combination of lidar digital relief model and simultaneous field control of the eliminated potential rockfall release and deposit areas. It should take place parallelly with field work of district foresters and forest planners. Preparation of rockfall hazard maps should become a mandatory part of forest management plans.
Keywords: porušitvena erozija; padajoče kamenje; varovalni gozdovi; skalni ponori; karta ogroženosti; Ajdovščina